THE INTERNALIZATION OF THE THREE PILLARS OF HIGHER EDUCATION THROUGH ACADEMIC COLLABORATION, INDUSTRY PARTNERSHIPS, AND GLOBAL COMMUNITY EMPOWERMENTA: Legal Perspective on Higher Education in the Era of Internationalization - Dwi Saleha; Achmad Rozi; Avinash Pawar (Amal Insani Foundation, 2026)
The internationalization of higher education represents a paradigmatic transformation that requires the integration of global dimensions into the implementation of the Three Pillars of Higher Education (Tri Dharma Perguruan Tinggi). This article analyzes the internalization of education and teaching, research, and community service through academic collaboration, industry partnerships, and global community empowerment from the perspective of Indonesian higher education law. This study employs a normative juridical approach through the analysis of statutory regulations and academic literature. The findings indicate that the successful internationalization of the Three Pillars necessitates legal certainty in cross-border cooperation, protection of intellectual property rights, strengthening of contractual governance, and harmonization of global academic ethical standards.